Behavioral Drivers of Capital Structure and Their Impact on MSE Performance: Evidence from Indonesia - Vebby Anwar; Andi Irwan; Muhammad Nabil Danial Bin Mohd Zaini; Rosdinaman Budi; Tasrim (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This study explores how financial behavior influences capital structure decisions and, in turn, affects firm financial performance and sustainable business growth among micro and small enterprises (MSEs) in Indonesia. Drawing on behavioral finance theory, the study examines the effects of three antecedents, financial literacy, risk tolerance, and behavioral biases on capital structure decisions. Furthermore, it investigates the mediating roles of access to finance and financial planning behavior, and the outcome effect of financial performance on long-term business growth. Method:Data was gathered from 420 MSE owner-managers across a variety of Indonesian sectors using a standardized questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data. Findings: Results revealed that all three behavioral antecedents significantly influenced capital structure decisions. Capital structure, in turn, had both direct and indirect effects on firm financial performance, mediated through improved financial access and planning. Moreover, financial performance was found to positively influence sustainable business growth. Novelty/Value:By relating behavioral characteristics to organizational outcomes and financial decision-making in the setting of an emerging economy, the study adds to the body of literature. Targeted financial education and behavioral interventions are necessary to improve financing results for MSEs, among other practical implications.